IMPLEMENTATION OF WEBSITE-BASED MANAGEMENT INFORMATION SYSTEMS IN SUPPORTING THE DIGITAL MADRASAH PROGRAM - Wahyudi, Kacung (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
The use of management information systems in education is necessary to optimize the information and completeness of an integrated system so that it will run effectively and efficiently. Over time the use of management information systems has developed in accordance with technological developments. This has changed the management of information systems that used to be manual to now digital-based management information systems. Research objectives: 1) Implementation of a website-based management information system in supporting of the digital madrasah program at MTsN 3 Pamekasan; 2) Factors of supporting and inhibiting the website-based management information system in supporting the digital madrasah program at MTsN 3 Pamekasan. This study uses qualitative research with a descriptive approach. Data obtained by semi-structured interviews, non-participant observation, and documentation. While the data sources are from school principals, educators, operators of management information systems, and curriculum assistants. While checking the validity of the data is done by triangulating sources and techniques, extending observations, and observing persistence. The results of this study indicate that first, the implementation of management in supporting the digital madrasah program at MTsN 3 Pamekasan is very effective and simplifies the management of management information systems, especially academic information systems, digital-based learning, digital libraries and evaluation of digital-based learning. Second, the supporting factors are the availability of complete facilities and infrastructure and most of the human resources have good technological capabilities. While the inhibiting factor is soft tissue. The solution is to provide a personal hotspot to keep the system usable